Advisory Opinion or Judgment? The Case of the Chagos Archipelago - Kuźniak, Brygida; Kabat-Rudnicka, Danuta (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2021)
The aim of this article is to provide an analysis of the ICJ’s advisory opinion of 25 February 2019 on the Chagos Archipelago. It will endeavour to answer the following questions: (i) is it consistent with the letter and the spirit of international law for the ICJ to issue advisory opinions in cases involving a dispute between states, which, due to the lack of consent from one of the states, cannot be brought before the ICJ and be settled by a judgment of that judicial body?; (ii) is such a ruling the right way to settle the issue of decolonization?; and (iii) did Brexit play any role in the case under discussion? The article begins by describing the background to the dispute between the UK and Mauritius. The focus of the analysis then shifts to the nature of advisory opinions and the 2019 ICJ advisory opinion on the Chagos Archipelago. Next, the authors discuss the possible impact of Brexit on the dispute between the UK and Mauritius itself, as well as on the UK’s international standing in general. The article concludes with reflections on voluntarism in international law. The authors conclude that de lege lata an authorized body or organization may ask the ICJ for an advisory opinion in situations where it believes that such an opinion would be useful for its work. However, such advisory opinions should not have the character of authoritative court statements made in pending disputes between sovereign states. As a consequence, such opinions should refer only to abstract legal problems, which means that in some cases the ICJ should refrain from issuing them.